Principle-Based Stepped Care and Brief Psychotherapy for Integrated Care Settings (Springer International Publishing, 2018)
This timely volume provides the practitioner with evidence based treatments for many of the clinical problems encountered in integrated care. It applies the core concepts of stepped care to integrating brief mental health interventions as a way to address ongoing problems in the modern healthcare landscape. It sets out in depth the state of the healthcare crisis in terms of costs, staffing and training issues, integration logistics and management, system culture, and a variety of clinical considerations. Central to the book is a best-practice template for providing behavioral stepped care in medical settings, including screening and assessment, levels of intervention and treatment, referrals, and collaboration with primary care and other specialties. Using this format, contributors detail specific challenges of and science-based interventions for a diverse range of common conditions and issues, including: Depression. Anxiety disorders. Adherence to chronic obstructive pulmonary disorder management. Alcohol and other substance misuse. Attention deficit hyperactivity disorder. Chronic pain. Neurocognitive disorders. Paraphilias: problematic sexual interests.[WU3] Sexual abuse and PTSD in children. A solid roadmap for widescale reform, Principle-Based Stepped Care and Brief Psychotherapy for Integrated Care Settings is deeply informative reading for health psychologists, social workers, psychiatrists, and clinical psychologists. It also clarifies the research agenda for those seeking improvements in healthcare quality and delivery and patient satisfaction. .